Copolymerization of Sulfur Chains with Vinyl Functionalized Metal−Organic Framework for Accelerating Redox Kinetics in Lithium−Sulfur Batteries (Adv. Energy Mater. 21/2022). Issue 21 (2nd June 2022) - Zeng, Qinghan; Li, Xin; Gong, Wei; Guo, Sijia; Ouyang, Yuan; Li, Dixiong; Xiao, Yingbo; Tan, Chao; Xie, Lin; Lu, Haibin; Zhang, Qi; Huang, Shaoming
Abstract : MOF/S Composite Cathodes In article number 2104074, Qi Zhang, Shaoming Huang and co‐workers propose an efficient strategy to elaborate sulfur cathodes by copolymerization between MOFs and sulfur chains. The radical reaction mechanism of the cathode derived accelerated polysulfides conversion restrains the shuttle effect and improves battery performance compared to traditional MOF/S composite cathodes at both low and high sulfur loadings.